2017
DOI: 10.2147/ppa.s143873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caregivers’ expressed emotion on the care burden and rehospitalization rate of schizophrenia

Abstract: BackgroundThis study assessed the effect of expressed emotion (EE) among caregivers of schizophrenia patients on their care burden and the illness rehospitalization rate.Subjects and methodsA total of 64 schizophrenia patients hospitalized for the first time and their key caregivers were recruited. The Chinese version of the Camberwell Family Interview (CFI-CV) was used to evaluate the EE of the key caregivers. A family burden questionnaire was used to evaluate the care burden. The patients’ rehospitalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
2
24
0
3
Order By: Relevance
“…Mental illness is upsetting and disabling conditions for patients which, in turn, causing a severe burden for their family and society [21]. Caring for a family member with schizophrenia has day-to-day challenges and requires adjustments on the part of relatives, especially in the first-onset of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Mental illness is upsetting and disabling conditions for patients which, in turn, causing a severe burden for their family and society [21]. Caring for a family member with schizophrenia has day-to-day challenges and requires adjustments on the part of relatives, especially in the first-onset of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent validity was measured using Spearman correlations with expected significant negative correlations with patient's function (GAF score), as well as significant positive correlations with caregiver's depression (PHQ-9 score), and anxiety symptoms (GAD-7 score) (Ji et al, 2014; Wang et al, 2017; Sun et al, 2018; Yu et al, 2018). We further performed Fisher r-to-Z test to compare the statistical significance of different correlations.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that within the psychosis population, high-EE is a predictor of relapse and rehospitalisation. Several studies have explored the needs, perceptions and mental health of carers supporting these individuals and found that high-EE is associated with high carer burden (Wang et al, 2017). Family members experiencing high burden were more likely to have higher levels of anxiety and depression and financial impairment (Barrowclough et al, 1996;Jansen et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Psychosis literature found that high-EE was associated with both higher carer burden and distress in family members" health (Wang et al, 2017;Jansen et al, 2015). Considering that family members of ARMS reported high levels of worry and concern (Wong et al, 2008), one may expect to see high-EE have a negative impact for ARMS families" health.…”
Section: Summary Of Findingsmentioning
confidence: 99%